Headlines in history the 1900s - Miller, James (Greenhaven press, 2001)
Offering thirty-three readings on key events in the history of the 1900s, this book focuses on scientific knowledge, assembly-line mass production, world wars, the Cold War, the danger of nuclear warfare, and political assassinations.